Reconsidering Sexual Identities: Intersectionality Theory and the Implications for Educating Counsellors - Cheshire, Liane (Canadian Journal of Counselling and Psychotherapy, 2012)
<span style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-CA; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Counselling programs in Canada provide minimal training relating to lesbian, gay, and bisexual (LGB) issues and cultures. This article presents a theoretical argument proposing that counselling programs move away from educating counsellors about LGB issues through specialized courses based on multicultural approaches of difference and diversity and move toward an approach based on intersectionality theory. Intersectionality theory presents social identities such as gender, race, class, and sexuality as mutually constituted, interconnected, fluid, and contextually specific. It is argued that feminist pedagogy can play a major role in integrating intersectionality theory throughout entire counselling programs and that this implementation would better equip counsellors to work with LGB clients.